Exegetical method a student's handbook - Kaiser, Otto; Kummel,Werner Georg; Goetchius, E.V.N. (New York, NY Seabury, 1967)
Includes bibliographical references.
originally published in German, 1963 Munchen, Kaiser Verlag.
Keywords: Bible -- criticsm, interpretation, etc..